Another shot at forever - Sheik, Hana (Harlequin romance, 2025)
When Zaynab shows up at her estranged husband's door, clutching divorce papers, she doesn't expect their goodbye to result in one final dazzling night of passion. But the bigger shock? She's pregnant! Determined to support Zaynab, Ara offers a convenient solution: move back in together until the baby's arrival. Only, being back in such tempting proximity to each other reignites the unresolved feelings they'd tried desperately to suppress... With just six months until Zaynab's due date, can they find a way to undo past mistakes--and give their marriage another shot?